2018
DOI: 10.1039/c7ra11619e
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical studies of resveratrol, methyl-jasmonate and cyclodextrin interactions: an approach to resveratrol bioproduction optimization

Abstract: The role of cyclodextrins in the bioproduction of resveratrol in the presence of methyl-jasmonate is rationalized, leading to solutions for the improvement of bioproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…First, 1 H DOSY NMR experiments also confirmed the interaction of MOR with α-CD due to variations in the diffusion coefficient D value as displayed in Figure 5 A. The diffusion coefficient can be linked to the translational motion of molecules in solution and its value depends on the size of the object [ 24 ]. The bigger the molecule is, the smaller the D value will be.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, 1 H DOSY NMR experiments also confirmed the interaction of MOR with α-CD due to variations in the diffusion coefficient D value as displayed in Figure 5 A. The diffusion coefficient can be linked to the translational motion of molecules in solution and its value depends on the size of the object [ 24 ]. The bigger the molecule is, the smaller the D value will be.…”
Section: Resultsmentioning
confidence: 92%
“…Excess amount of MOR were added (20 mg) to a 0.6 mL D 2 O solution containing different α-CD concentrations (from 10 to 50 mM). The suspensions were maintained at 300 K for 24 h, filtered through 0.2 µm cellulose filters from Grace (Columbia, MD, USA) and analysed by a 1 H-NMR quantitative experiment called ERETIC [ 24 ]. First, a 1 H-NMR experiment using zg pulse program (D1 5 s, AQ 4.54 s, TD 64K, NS 8) with a Bruker reference standard triphenylphosphate (TPP) (48.5 mM in aceton-d6)was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio MeJA concentration/biomass is a key element to understand resveratrol production, and the optimal ratio observed in this work was 0.125 mmol/g DW. Furthermore, it has been shown that the solubility of MeJA in the water liquid medium could be enhanced by its complexation with cyclodextrins, and then provoked the highest elicitation response [41].…”
Section: Optimization Of Meja Elicitation In Flask Experimentsmentioning
confidence: 99%
“…This could suggest a potential phenomenon of aggregation of β-CD(C9)2OOMe 1 in aqueous medium. In order to study the dipolar interactions between protons of the CD cavity and those of the fatty chains, a T-ROESY NMR experiment was performed on β-CD(C9)2OOMe 1 in D2O ( Figure 5) [42]. Strong cross-correlation peaks between alkyl protons and protons of CD moiety have been observed revealing interactions of the grafted chains with the CD cavity.…”
Section: Self-organization Propertiesmentioning
confidence: 99%